A Water-Centric Approach in the Assessment and Governance of the Water-Energy-Climate Change Nexus in South Africa - Mathetsa, Steven Matome; Simatele, Mulala Danny; Rampedi, Isaac T. (Frontiers in Sustainable Food Systems, 2022)
Water and energy interdependency, in the context of climate change, threatens security of these resources. Anecdotal evidence suggests that risks associated with the ‘Water-Energy-Climate Change’ (WECC) nexus will affect all subsectors of the economy. Yet the WECC nexus has not received commensurate attention in research and policy. Some countries have begun identifying avenues to understand and forestall WECC impacts, but less so in developing countries. This has compromised the adaptive capacity and resilience of developing countries’ economies to WECC impacts. This paper analyses existing literature, historical and contemporary secondary data on climate change, water and energy interdependency in South Africa. It outlines the interlinkages and implications of these three components on each other, particularly within the discourse of sustainable water resource management. The paper recommends water-centric approach to improve evidence-based institutional and policy framework to address the myriad challenges of this nexus in a holistic and integrated manner.